Pengaruh Kompetensi Sumberdaya Manusia terhadap Kualitas Laporan Keuangan Daerah Pemerintah Provinsi Jambi melalui Pemanfaatan Teknologi Informasi sebagai Variabel Intervening - Faramitha Riskia; Fitrini Mansur; Misni Erwati (Ekonomis: Journal of Economics and Business, 2022)
This study aimed to determine the effect of human resource competence on the quality of regional financial reports at the Jambi Provincial Government through the utilization of information technology. The populations in this study were officials at the Regional Apparatus Organization within the Jambi Provincial Government which functions as accounting entities involved in regional financial management and reporting. The sample in this study was selected by using the judgment sampling method, namely officials authorized in the management and reporting of regional finances from 19 OPD in the Jambi Provincial Government. Data analysis in this study used the Partial Least Square (PLS) approach with the help of Smart PLS 3.0 software. The results of this study indicated that HR competencies had a direct influence on the utilization of information technology and the quality of regional financial reports. The results of this study also indicated that the competence of human resources had an indirect influence on the quality of regional financial reports at the Regional Government Organization of Jambi Province through the utilization of information technology.